Umbilical Cord Artery Mechanical Properties at Various Gestational Ages - Nye, Kevin S.; Esplin, M. Sean; Monson, Kenneth L. (American Journal of Perinatology, 2015)
Objective Umbilical cord tissue is naturally available after birth and may provide insight into the health of a newborn. Intraventricular hemorrhage (IVH) is a common complication of prematurity that is suspected to be associated with structural deficiency of the vasculature. We are interested in determining whether umbilical vessel properties could be used to indicate increased risk for IVH. As a first step toward this, we investigated umbilical artery properties as a function of gestational age.Study Design A total of 31 umbilical cord specimens were collected from births ranging from 24 to 40 weeks gestation. Specimens were grouped according to gestational age (less than 25, 26–30, 31–35, and 36–40 weeks). Tension tests were performed on axial and circumferential strips obtained from umbilical arteries. Stiffness, corresponding stretch values, and cross-sectional tissue areas were compared using analysis of variance.Results Stress-stretch curves displayed no apparent differences across the gestational age range. Statistical analysis of stiffness and stretch values suggested no differences between groups (p > 0.05). Significance was shown between cross-sectional areas of some groups.Conclusions Mechanical characterization of umbilical arteries suggests that no significant changes in material properties occur in the range of 24 to 40 week gestational age.
Keywords: umbilical artery; mechanical properties; intraventricular hemorrhage; neonate